2021
DOI: 10.1021/acs.est.0c06907
|View full text |Cite
|
Sign up to set email alerts
|

New Role for a Commercially Available Bioinsecticide: Bacillus thuringiensis Berliner Biodegrades the Pyrethroid Cypermethrin

Abstract: The microbial diversity of several environments has been explored by researchers for the biodegradation of pyrethroids. In this study, a new approach was employed aiming at the use of Bacillus thuringiensis Berliner, a strain commercially available as bioinsecticide, for Cypermethrin (Cyp) biodegradation. This bacterial strain grew in the presence of Cyp and biodegraded this xenobiotic in a liquid medium. A central composite design for surface response methodology was employed for biodegradation. Under optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…However, the results of our research cannot be directly compared with those of the recent studies on the capacity of PYR degradation by other isolated strains, since the experiments were carried out under the abiotic conditions over a short period of time, but it provides favorable support for developing enzyme preparations that can be industrially produced. According to the study reported by Birolli et al (2021) , only 16.7% CYP degradation was determined under abiotic conditions, whereas 36.6 ± 1.9% biodegradation was observed for B. thuringiensis Berliner with the native microbiome. The example evidently indicated that bioaugmentation with the bacterial strain promoted a significant increase in the pesticide decontamination, prompting that Est804 can be used in biological conditions to enhance the degradation of pyrethroids, which is possibly of great benefit for application in agricultural residue treatment and environmental remediation.…”
Section: Resultsmentioning
confidence: 88%
“…However, the results of our research cannot be directly compared with those of the recent studies on the capacity of PYR degradation by other isolated strains, since the experiments were carried out under the abiotic conditions over a short period of time, but it provides favorable support for developing enzyme preparations that can be industrially produced. According to the study reported by Birolli et al (2021) , only 16.7% CYP degradation was determined under abiotic conditions, whereas 36.6 ± 1.9% biodegradation was observed for B. thuringiensis Berliner with the native microbiome. The example evidently indicated that bioaugmentation with the bacterial strain promoted a significant increase in the pesticide decontamination, prompting that Est804 can be used in biological conditions to enhance the degradation of pyrethroids, which is possibly of great benefit for application in agricultural residue treatment and environmental remediation.…”
Section: Resultsmentioning
confidence: 88%
“…In it, compounds G and K have not been reported in the biodegradation process of fenvalerate. However, 3-aminobenzoic acid has been detected in the biodegradation products of beta-cypermethrin [ 46 ]. Moreover, 3,4,5-trihydroxybenozic acid was detected in the products obtained from the degradation of 3-PBA by strain M-4 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Refreshment of bacterial isolates was carried out by growing a loopful of HSFI-12 bacterial colony on Nutrien Agar (NA) growth media. The media was incubated in an incubator (Memmert, Germany), at 37ºC for 24 h (Birolli et al, 2021) . The growing colonies were then observed under an optical microscope (Olympus, Japan) for their uniform cell morphology (Purwaningrum et al, 2021) .…”
Section: Subculture Of Bacillus Thuringiensis Hsfi-12mentioning
confidence: 99%